The System of Proving Zina in Aceh Qanun from the Perspective of Maqashid Sharia - Muhammad Aulia Ramdan Daenuri; Dzulkifli Hadi Imawan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The provisions on proving zina in the Aceh Qanun have drawn pros and cons in society, particularly regarding the confession of adultery as stated in the MS Idi decisions Number 3/JN/2021/MS.Idi and Number 4/JN/2021/MS.Idi. According to the Aceh Qanun, a defendant's confession in proving adultery applies only to the defendant and cannot implicate their partner. The purpose of this study is to compare the system of proving adultery in the Aceh Qanun with the provisions of Islamic jurisprudence, and to analyze and evaluate these provisions from the perspective of maqashid sharia. This research is a normative legal research, referring to legal norms contained in legislation, judges' decisions, and doctrines obtained through literature. The findings indicate that the system of proving adultery in the Aceh Qanun is consistent with maqashid sharia, particularly in protecting honor (hifdz al-‘ird) and lineage (hifdz al-nasl). Adultery is considered a serious offense that can severely damage an individual’s social standing. Therefore, strict evidentiary standards are essential to prevent false accusations and social harm. If the requirements for proving adultery were loosened, it would increase the risk of abuse and defamation. Accordingly, the Aceh Qanun provision that imposes hadd qadzaf—eighty lashes—on those who accuse others of adultery without presenting four witnesses is justified and necessary. The author hopes that this research can contribute academically in the development of Islamic law and its application in Indonesia, especially in the maqashidi approach to the system of proving adultery in the Aceh Qanun.